Sistem Kendali Fertigasi Presisi Berbasis Logika Fuzzy untuk Budidaya Tanaman Hidroponik - Haryo Prastono; Mohamad Solahudin; Supriyanto Supriyanto (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
The fertigation control system has been extensively developed, particularly for hydroponic plant cultivation. However, existing studies often overlook the characteristics of the interaction between the environment and plants. Evapotranspiration and the moisture status of the growing medium are two critical parameters in determining the volume of fertigation. As a control system, fuzzy logic can manage fertigation based on these two parameters. This study aims to deliver water and nutrients to plants more effectively and efficiently, aligning with current environmental conditions and plant needs. The research was conducted through several stages: defining design criteria, creating a fuzzy logic design, simulating the fuzzy logic-based fertigation control system, and testing the system. Simulation results indicate that when the moisture content of the growing medium is between 26% and 31%, the fertigation duration varies according to evapotranspiration values. When the moisture content exceeds 32%, fertigation does not occur regardless of evapotranspiration values. Testing results demonstrate that the fuzzy logic used in this control system is efficient in delivering fertigation, as evidenced by minimal runoff compared to systems without control. Additionally, the moisture status of the growing medium consistently remains within the available water zone or at the optimum condition for plant water absorption, with a mean absolute percentage error of 1.98%. The designed fuzzy logic control system is also effective in providing fertigation, with the total volume ranging from 132 to 308.4 ml/day, closely matching the daily evapotranspiration rate. Based on plant physiological measurements, the fuzzy logic control system outperforms fertigation without control.